PENGOPTIMALAN BLOG DALAM UPAYA MENUNJANG KETERAMPILAN MENULIS MAHASISWA - Kurniawan, Latif Anshori (SASINDO, 2014)
The data used to say that the writing skill of students are still poor. Based on thiscase, there is an idea to maximize blog as a solution in an effort to optimize the writingskill of students. In this paper, the authors found the potential of blog as solutions toimprove the writing skill of students. The key focus of this paper is to determine thepotential of blog in order to optimize the writing skill of students which is evenexpected to support other language skills. Finally, blog has a potential solutionâin aneffortâto push the writing skills of students.Keywords: blog, writing skill